2017
DOI: 10.3389/fpls.2017.00309
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation of Leaf Optical Properties in a Boreal Forest Is Influenced by Species and Light Environment

Abstract: Leaf Optical Properties (LOPs) convey information relating to temporally dynamic photosynthetic activity and biochemistry. LOPs are also sensitive to variability in anatomically related traits such as Specific Leaf Area (SLA), via the interplay of intra-leaf light scattering and absorption processes. Therefore, variability in such traits, which may demonstrate little plasticity over time, potentially disrupts remote sensing estimates of photosynthesis or biochemistry across space. To help to disentangle the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 47 publications
6
33
1
Order By: Relevance
“…This is in line with earlier studies that have emphasized importance of species and needle age over light environment (Knapp and Carter 1998;O'Neill et al 2002;Atherton et al 2017). On the other hand, Lukeš et al (2013) observed differences in coniferous needle reflectance between canopy positions, which were much larger than those observed in our study.…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with earlier studies that have emphasized importance of species and needle age over light environment (Knapp and Carter 1998;O'Neill et al 2002;Atherton et al 2017). On the other hand, Lukeš et al (2013) observed differences in coniferous needle reflectance between canopy positions, which were much larger than those observed in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Needle age (current-year vs. previous-year needles), on the other hand, explained up to 37% of the total variance in measured transmittance for the same set of species. In addition, canopy position, and thus light environment, had a relatively small influence on needle spectra [11], which is in line with other studies that have emphasized importance of species and needle age over light environment [17,47]. On the other hand, in another study limited to three species, larger differences in coniferous needle reflectance were indeed observed between canopy positions [27].…”
Section: Spatial Variation In Needle Spectrasupporting
confidence: 88%
“…The average lifespan, defined as the leaf age-class retaining at least 50% of leaves, varies for coniferous species from 6 to 110 months [46]. Spectral differences within coniferous crowns are mainly observed (1) between needles of different age, and (2) between vertical canopy layers with different levels of adaptation to direct/diffuse radiation conditions [11,17,27,47]. For example, current-year Norway spruce needles collected from a study site in the Czech Republic (see Appendix B for details) show the largest spectral differences between two vertical canopy levels, whereas older cohorts of needles exhibit almost no differences in their spectral properties (Figure 2).…”
Section: Spatial Variation In Needle Spectramentioning
confidence: 99%
“…For example vertical and horizontal gradients in leaf level biophysical parameters could be assigned, which are known to occur in actual canopies in response to light environment (Atherton et al, 2017). Additionally, background and branch influences on canopy SIF simulation can also be simulated based on this method.…”
Section: Discussionmentioning
confidence: 99%
“…Although measureable from space and aircraft, SIF originates close to the site of the photosynthetic reactions, and is therefore closely linked to plant growth and physiological status. Unlike the traditional reflectance vegetation indices, such as the Normalized Different Vegetation Index (NDVI), SIF responds very rapidly to environmental stress, and therefore has the potential to track time-varying stress at (sub) diurnal scales (Amoros-Lopez et al, 2008;Yang et al, 2015;Alonso et al, 2017).…”
Section: Introductionmentioning
confidence: 99%